Effects of ageing on the eye structure and function 2019 - Cerviño, Alejandro (2020)
[Excerpt] The world’s population is growing older, with persons over the age of 65 being the fastest-growing age group. According to data from World Population Prospects 2019 [1], one in 11 people in the world was over the age of 65 in 2019 (9%), and this number is expected to increase to one in six (16%) by 2050 since life expectancy is also expected to increase from current 72.6 years to 77.1. In 2018, for the first time in history, persons aged 65 or above outnumbered children under five years of age.[...]